Evaluación de la calidad del servicio y su impacto en el nivel de satisfacción de los clientes de la corporación Jarrin Herrera cía. Ltda., sucursal Quevedo, año 2023 - Toala Manjarrez, Eylin Juliana (2024)
The research study entitled “Evaluation of service quality and its impact on customer satisfaction at Corporation Jarrín Herrera Cía. Ltda., Quevedo branch, year 2023”, is essential to ensure customer satisfaction and maintain competitiveness in the market. Factors such as staff training and commitment, customer service, efficiency in product delivery, and effective problem solving influence this evaluation. The main objective is to evaluate how service quality affects customer satisfaction. The research approach is explanatory, field and correlational, using inductive, deductive and analytical methods. The sample included 341 individuals, including the administrator, salesmen and clients of Corporation Jarrin Herrera Cía. Ltda. The results show that the clients consider the service to be satisfactory, but there are opportunities for improvement to achieve excellence. It is essential to invest in team development and promote a positive work environment to maintain high standards of service. The identification of detractors through NPS analysis can improve reputation and foster customer loyalty, the conclusion is that service quality is directly related to customer satisfaction and staff commitment, key aspects for the success and competitiveness of the company.